Healthcare and Management Practices among Pig farmers in hill zone of West Bengal - ROY, RAKESH (Indian Journal of Hill Farming, 2015)
Pig is one of the most efficient feed and feed byproduct converter with higher growth potential and short generation interval among the domesticated livestock species. The study was undertaken to find out the healthcare and management practices in backyard pig rearing. The present study was conducted purposively in the hill zone of West Bengal assuming large pig population. In all, 120 respondents were the total sample size for the study. The study shows that majority of the respondent had observed diarrhoea as the most prevalent disease but none had segregated infected animals from the healthy stock. Majority of the respondents treated their sick animals by themselves using indigenous traditional knowledge. Little attention was paid to deworming and vaccination against important disease by the majority of the respondents. The study also reveals that majority of the respondents had a wooden or bamboo house for their pig, used broom only for cleaning the house. Neither of them gave iron and vitamin for their piglets nor did they provide separate house, bedding material or practiced weaning. Little attention was paid to supplementary feeding and care for mortality prevention in piglets. Majority of the respondents castrated boar by an expert in the village using an indigenous method between 3-6 months, but none of the respondents were found removing the needle teeth.